Reflections from a Feminist Pedagogy Perspective. Overcoming Gender Blindness within Economic Sciences - Pagura, María Fernanda (Ediciones UNL. Secretaría de Extensión de la UNL, 2021)
As it has been demonstrated by numerous research works, discourses and educational practices in university produce knowledge and dictates of conscience which are penetrated by androcentrism and sexism: Economics and Administration are not the exception. Making the disciplinary approachof social issues from a gender perspective more complex invites us to understand the world from the point of view of power relationships which are expressed in social, economic, political and sexual injustice niches. In order to achieve this, it is necessary to analyze not only what is said about the world in terms of discourse but also the procedures which play a role in scientific production. Therefore, an epistemic and methodological criticism of the predominant focus within such disciplines constitutes an essential step towards the development of a feminist perspective in the Schools of Economic Sciences.This paper revisits, from a gender point of view, the experiences of the last two years of the subject ‘Research Methodology’ from the third year of the bachelor’s degree in Economics and in Administration of Universidad Nacional del Litoral (Santa Fe, Argentina). Firstly, we are interested in showing the feminist epistemic positioning which is expressed in the didactic and pedagogical proposal of the subject and which also considers students’ impressions. Secondly, we would like to explicitly state some forms of materialization of sexism within the prescribed, hidden and null curriculum in professional education